Manajemen Pendidikan dalam Hadis Tarbawi : Panduan Ilmiah dan Spiritual Bagi Pendidik Muslim - Asip Ependi; Ahmad Ilham Fadli; Ahmad Fatoni (Pusat Riset dan Inovasi Nasional, 2025)
Educational management in the Islamic perspective is not only administrative but also spiritual and scientific. Hadis Tarbawi, as part of the Islamic heritage, offers managerial principles that can be applied in education, ranging from planning and implementation to evaluation. This study aims to reveal the managerial content in Hadis Tarbawi that can serve as a guide for Muslim educators. Using a qualitative approach and literature review method, this research analyzes selected hadiths related to educational values. The findings show that Hadis Tarbawi contains key principles such as just leadership, effective communication, character development, continuous evaluation, and spirituality in managing the educational process. These insights enrich the scientific literature in the field of Islamic educational management and offer a more holistic approach to managing education. The study recommends integrating Hadis Tarbawi into the Islamic education curriculum and providing training for educators to apply these principles in practice.